2023
DOI: 10.3390/v15091912
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 and N-803 for HIV Cure Approaches

J. Natalie Howard,
Alberto Bosque

Abstract: In spite of the advances in antiretroviral therapy to treat HIV infection, the presence of a latent reservoir of HIV-infected cells represents the largest barrier towards finding a cure. Among the different strategies being pursued to eliminate or reduce this latent reservoir, the γc-cytokine IL-15 or its superagonist N-803 are currently under clinical investigation, either alone or with other interventions. They have been shown to reactivate latent HIV and enhance immune effector function, both of which are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
1
4
0
Order By: Relevance
“…In vivo studies and clinical trials have indicated that IL-15 or N-803 alone are unlikely to provide sufficient latency reversal activity but have highlighted their potential as a component of combination treatments. This is supported by observations of immune restorative effects of IL-15 or N-803 treatment that may support the clearance of reservoir cells [261][262][263].…”
Section: Latency-reversing Agents In Combinationsupporting
confidence: 54%
See 1 more Smart Citation
“…In vivo studies and clinical trials have indicated that IL-15 or N-803 alone are unlikely to provide sufficient latency reversal activity but have highlighted their potential as a component of combination treatments. This is supported by observations of immune restorative effects of IL-15 or N-803 treatment that may support the clearance of reservoir cells [261][262][263].…”
Section: Latency-reversing Agents In Combinationsupporting
confidence: 54%
“…A recent study combining a Smac mimetic with the IL-15 superagonist N-803 and RhmAbs reported latency reversal and a reduction in reservoir size in SIV-infected rhesus macaques upon treatment [246]. While the impact of N-803 on latency reversal in this study was modest, the use of IL-15 or N-803 as a part of cure strategies has been studied extensively (reviewed in [261]). In vivo studies and clinical trials have indicated that IL-15 or N-803 alone are unlikely to provide sufficient latency reversal activity but have highlighted their potential as a component of combination treatments.…”
Section: Latency-reversing Agents In Combinationmentioning
confidence: 75%
“…No evidence that coronavirus disease 2019 mRNA vaccination induces detectable viremia HIV pVL testing was performed at the baseline visit, which occurred a median of 12 (IQR 3-26) days prior to vaccination, one month (a median of 31 [IQR [29][30][31][32][33] days) after the first vaccine dose, and again one month (a median of 30 [IQR 29-30] days) after the second vaccine dose (Fig. 1).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…This could theoretically occur via direct stimulation of reservoir cells that recognize the vaccine antigen, including naïve CD4 + T-cell reservoirs [ 25 , 26 ] specific for SARS-CoV-2 Spike, or existing cross-reactive memory CD4 + T-cell reservoirs specific for common cold coronavirus antigens [ 27 , 28 ]. Alternatively, reservoir stimulation could occur through a generalized inflammatory response with cytokine production [ 29 , 30 ] that could transiently promote HIV gene expression in bystander reservoir cells that are not specific to the vaccine antigen [ 31 ]. Indeed, reports of increased HIV viremia in individuals receiving ART following COVID-19 mRNA vaccination have emerged [ 31 33 ], though other studies have observed no such effects [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In research using a mouse tumor model, hematopoietic stem cell (HSC)-derived CAR-NK cells have shown exceptional anti-tumor efficacy in combination with nivolumab 50 . N-803, an IL-15 superagonist, has been shown to expand NK cells in humans after injection and to be well tolerated 51 . An ongoing clinical trial (NCT04847466) 52 is investigating the combination of N-803, pembrolizumab, and HSC CAR-NK for the treatment of GEJ and advanced HNSCC; trial completion is expected by the end of 2025.…”
Section: Traditional Icismentioning
confidence: 99%